1989
DOI: 10.1021/bi00436a007
|View full text |Cite
|
Sign up to set email alerts
|

Mouse steroid 15.alpha.-hydroxylase gene family: identification of type II P-45015.alpha. as coumarin 7-hydroxylase

Abstract: We identified type II P-450(15)alpha as mouse coumarin 7-hydroxylase (P-450coh). Unlike type I P-450(15)alpha, the other member within the mouse steroid 15 alpha-hydroxylase gene family, type II catalyzed little steroid 15 alpha-hydroxylase activity, yet structurally there were only 11 substitutions between type I and type II P-450(15)alphaS within their 494 amino acid residues (Lindberg et al., 1989), and the N-terminal sequence (21 residues) of P-450coh was identical with that of both P-450(15)alphaS. Induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(45 citation statements)
references
References 21 publications
2
43
0
Order By: Relevance
“…Similarly, the level of CYP2A5 protein could not be determined in the OM by immunoblot analysis, because the antibody also reacted with CYP2G1. Subsequently, the relative levels of CYP2A5 enzyme in the 129/Sv and Cyp2g1-null strains were estimated by a determination of microsomal activities in coumarin 7-hydroxylation, which is specific for CYP2A5 (Negishi et al, 1989). As shown in Table 2, the extent of decrease in coumarin 7-hydroxylase activities in liver and kidney of the Cyp2g1-null mice was more or less similar to the extent of decrease of the CYP2A5 mRNA levels shown in Table 1.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, the level of CYP2A5 protein could not be determined in the OM by immunoblot analysis, because the antibody also reacted with CYP2G1. Subsequently, the relative levels of CYP2A5 enzyme in the 129/Sv and Cyp2g1-null strains were estimated by a determination of microsomal activities in coumarin 7-hydroxylation, which is specific for CYP2A5 (Negishi et al, 1989). As shown in Table 2, the extent of decrease in coumarin 7-hydroxylase activities in liver and kidney of the Cyp2g1-null mice was more or less similar to the extent of decrease of the CYP2A5 mRNA levels shown in Table 1.…”
Section: Resultsmentioning
confidence: 81%
“…In this regard, because the decrease in CYP2A5 expression did not reduce systemic AP clearance or the extent of AP hepatotoxicity, we were able to use the Cyp2g1-null mice to probe the role of CYP2G1 in AP nasal toxicity. On the other hand, although OM coumarin toxicity is likely mediated by CYP2G1, this hypothesis was not tested in the current study, because CYP2A5 is the major coumarin hydroxylase in the liver (Negishi et al, 1989), and because the Cyp2a5 gene has a strain-related genetic polymorphism that significantly affects coumarin hydroxylase activity (Lindberg et al, 1992). It is likely that the impact of an altered hepatic CYP2A5 expression on OM toxicity will be less worrisome for compounds delivered through the nose.…”
Section: Cyp2g1-null Mice 725mentioning
confidence: 90%
“…Recent studies have also indicated that in the mouse P450IIA proteins are highly inducible by pyrazole and to a lesser degree by phenobarbital (33). It is interesting that P450IIA proteins catalyze coumarin hydroxylation (34,35) and that AFB1 also contains the coumarin structure. The apparent inducibility of many of the P450s involved in AFB1 metabolism suggests that the relative importance of specific forms in its activation will be determined by environmental and/or hormonal factors.…”
Section: Discussionmentioning
confidence: 99%
“…A decreased olfactory toxicity has been demonstrated after pretreatment with various P450 inhibitors (Brandt et al, 1990;Genter et al, 1994;Bahrami et al, 2000b). Many olfactory toxicants and carcinogens, including dichlobenil, coumarin, hexamethylphosphoramide, and the tobacco-specific 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone are preferentially bioactivated to reactive intermediates by the predominantly expressed mouse CYP2A5 (Negishi et al, 1989;Liu et al, 1996;Thornton-Manning et al, 1997;Gu et al, 1998;Zhuo et al, 1999;Felicia et al, 2000).2,6-Dichlorophenyl methylsulfone (2,6-diClPh-MeSO 2 ) ( Fig. 1) is a potent olfactory toxicant in rodents, and similar 2,6-dichlorobenzene derivatives with a large, polar, and strong electron-withdrawing substituent in the primary position have recently been reported as potential olfactory toxicants in mice (Brandt et al, 1990;Bahrami et al, 1999Bahrami et al, , 2000aCarlsson et al, 2004).…”
mentioning
confidence: 99%